Strategy of Islamic political jurisprudence invitationalism and diplomacy in making internationals safety - Akhlaghi, Abdolrahim (2021)
The present article is based on that using jurisprudential texts, the strategy of invitation and diplomacy can be proposed to improve the international security situation. The strategy of invitation and diplomacy seeks to persuade the other party to the correctness of an idea, policy and action. In other words, this strategy does not seek to suppress the actor on the other side, but through dialogue and diplomacy, the will to accompany, replaces the will to oppose. Since conflict is a feature of international relations¸ the interests of international actors are often at odds with each other, in which case diplomacy avoids any military confrontation or war by reducing the level of conflict.  Applying a conversation and invitation strategy means that in its interactions with other governments, the Islamic State seeks to use tools such as diplomacy, negotiation, consultation, increased cooperation with other countries, and the promotion of cultural interactions with the aim of increasing understanding at the international level. Islamic political jurisprudence, by laying foundations such as the Treaty of Amman at the height of the conflict between the Islamic State and the state and non-Muslim communities, makes it possible to reopen the horizons of diplomacy. The rule of compiling hearts with the aim of persuading and attracting hearts in the foreign interactions of the Islamic State is another principle that is also proposed in the same direction of the strategy of invitation and diplomacy. This strategy can be extracted with an inferential approach to jurisprudence.